Galectin-3 Overexpression in Invasive Laryngeal Carcinoma, Assessed by Computer-assisted Analysis - Miranda, Fabiana A.; Hassumi, Marcela K.; Guimaraes, Marcia C. M.; Simoes, Renata T.; Silva, Tarsia G. A. [UNESP]; Lira, Regia C. P.; Rocha, Ana M.; Mendes, Celso T.; Donadi, Eduardo A.; Soares, Christiane P. [UNESP]; Soares, Edson G. (Histochemical Soc Inc, 2009)
The larynx is the most common site of malignancy in the upper aerodigestive tract. In Brazil, malignant laryngeal lesions represent 2% of all cancers, with similar to 3000 annual deaths. The association between human papillomavirus (HPV) and laryngeal cancer is still controversial. The aim of the present retrospective study was to determine the expression of galectin-3 immunoperoxidase in laryngeal carcinoma by examining paraffin-em bedded larynx biopsies from 65 patients, 10 in situ laryngeal carcinomas, 27 laryngeal carcinomas without metastases, and 28 with metastases. Twenty-eight cervical lymph nodes from patients with metastatic lesions were also evaluated. Nested PCR was performed to detect and type HPV DNA. Galectin-3 expression was assessed by immunohistochemistry using a computer-assisted system. Among 65 patients, 55 (84.6%)were positive to beta-globin (internal control); 10 (15.4%) patients were beta-globin negative and were excluded from the HPV evaluation. Thus, 7 (12.7%) out of 55 patients were HPV positive and 48 (87.3%) out of 55 patients were HPV negative. High expression of galectin-3 was observed in invasive laryngeal tumors, suggesting that galectin-3 could be associated with the invasiveness and aggressiveness of laryngeal carcinomas. (J Histochem Cytochem 57:665-673, 2009)
Keywords: galectin-3; human papillomavirus; laryngeal carcinoma; immunohistochemistry; PCR